The Effect of Audit Quality, Debt Defaults and Audit Tenure on Going Concern Audit Opinions (Case Study of the Infrastructure, Transportation, and Utilities Sector Listed on the Indonesia Stock Exchange 2016 - 2018) - indah suryani (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
This study aims to examine the effect of debt default, audit tenure and audit quality towards going concern opinion. The samples used in this study are companies in the infrastructure, transportation and utility sectors listed on the Indonesia Stock Exchange in 2016-2018. The population of this study was 72 companies. The research sample was 24 which were selected by purposive sampling method with an observation period of 3 (three) years. Data were analyzed using logistic regression analysis model. The results showed that audit quality had an effect toward going concern audit opinion acceptance, while debt default and audit tenure had no effect toward going concern audit opinion acceptance